RANCANG BANGUN ALAT PENGUKUR SUHU DAN HAND SANITIEZER - Nursifaun Nikmah; Imam Sucahyo; Meta Yantidewi (Universitas Negeri Gorontalo, 2022)
This study aims to make a temperature measuring device and an automatic hand sanitizer using the MLX90614 sensor, which functions as a body temperature detector, Arduino Uno as a microcontroller which is then displayed on a 16x2 LCD and is equipped with a buzzer as an alarm sign if the temperature exceeds normal limits. The results obtained from measuring body temperature on the back of the hand produce an average value of 36.20 with an average tool error of 0.21% and an instrument accuracy of 99.79%. While the measurement of body temperature on the forehead obtained an average of 36.36 and an average error of 0.47%. Thus, Therefore, the tool is 99.53% accurate. Sensor sensitivity is affected by distance. The further away the sensor is from the object, the sensitivity of the sensor will decrease.